THE INTERVENSI TRAKSI SHOULDER LEBIH EFEKTIF DIBANDINGKAN DENGAN PENGULURAN PASIF PADA TERAPI KOMBINASI MWD-TENS TERHADAP PENINGKATAN LINGKUP GERAK SENDI BAHU PENDERITA FROZEN SHOULDER DI RSUD KABUPATEN BULELENG - Suadnya, I Wayan (Majalah Ilmiah Fisioterapi Indonesia; Vol 1 No 3 (2013): Majalah Ilmiah Fisioterapi IndonesiaDO - 10.24843/MIFI.2013.v01.i03.p01)
This research which is held at Medical Rehabilitation Department of General Hospital Buleleng Regency is aimed at determining the effectiveness of combination therapy between MWD, TENS and passive stretching and MWD, TENS and traction of shoulder toward the ROM of patients' shoulder who suffered from frozen shoulder. The research sample included 20 patients which was chosen using purposive random sampling technique and were collected from April 2011 until June 2011. This sample was divided into two groups with different therapy for each group. MWD, TENS and passive stretching treatment was given for group I and MWD, TENS and traction of shoulder was given for group II. The effectiveness of therapy was measured using Universal Goniometer. Both therapy increase the circulation of blood that give impact on pain reduction and muscle relaxation which is followed by muscle spasm reduction so that increasing ROM of patients. The data was analyzed using t-test (paired sample test). The result show that there is significant improvement of ROM at group I between before and after therapy with p = 0.000 (p < 0.05) at each of ROM. Significant improvement of ROM also found at group II between before and after therapy with p = 0.000 (p < 0.05) at each of ROM. The result also shown that there is significant difference of ROM between group I and group II with p =0.000 (p < 0.05). MWD, TENS and traction of shoulder which was treated at group II more effective than MWD, TENS and passive stretching which was treated at group I.